PERAN KOMUNIKASI INTERPERSONAL DALAM MENINGKATKAN PUBLIC SPEAKING PADA MAHASISWA KPI ANGKATAN 9 IAI AL-AZIS - Najah Fathin Nur Afsharina; Ahmad Asrof Fitri; Muhammad Nur Kholish Abdurrazaq (STKIP Subang, 2024)
In the competitive global era, this ability is a must to prepare for the world of work and achieve academic and social success. Public speaking skills are an important skill for students, especially in the Islamic Communication and Broadcasting (KPI) study program. However, many students still face obstacles such as lack of confidence. Interpersonal communication, which involves verbal and non-verbal interactions, plays an important role in building relationships and supporting the development of public speaking. The results show that openness, empathy, and active listening help students of KPI IAI Al-AZIS in social interactions and public speaking. Self-disclosure, social support, introspection, and concentration strengthen relationships with the audience, enhance self-confidence, and support effective and impactful communication. This research emphasizes the role of interpersonal communication in the development of students' public speaking skills.. Keywords: Interpersonal Communication, Public Speaking, Student